REALISME PERIKLANAN DAN PEMBENTUKAN IDENTITAS MASYARAKAT DALAM WACANA NEOLIBERALISME - Andrine Prima Afneta Arzil (SEMIOTIKA: Jurnal Komunikasi, 2014)
Identity is no longer determined by the peer group but is determined by mass media, including advertising. Advertising is a very powerful form of social communication in modern society. Comercial realism is trying to present the world in ways that could be real. Redistribution matters (neoliberalism concept) make advertisers create pleasurable emotions and false need that will be triggered when the product is viewed in the marketplace. In our consumer culture, we live in a world saturated with advertising imagery urging us to buy and consume products as a path to “future happiness” and self and identity-transformation.Keywords : Commercial Realism, Neoliberalism, Society Identity